Fibroblastic tumors - Cassinelli, Juan Fco; Falconi, Luis M (Cirugía del Uruguay, 1973)
ibroblastic tumors constitute an important sector within the vast subject of fibromatous proliferations. They are of special importance in soft parts because of their frequency, difficulty and complexity of nosogenic interpretation and of diagnostic and therapeutic problems due to their contradictory morphological characteristics and, at times, paradoxic biology. De-moid fibromas, fibromatosis, nodular fas.itis and dermic pseudosarcoma are, together with loca!ly -malignant, metastasis- producing orthodox fibrosarcoma, the most significant processes in this chapter of tumors of soft parts. These forms have un